Upper airway obstruction and dyspnea in an infant caused by mediastinal and endotracheal lipoblastoma: a case report - Chen, Yulin; Qiu, Li; Kou, Wei; Liu, Zhongqiang (Frontiers in Oncology, 2025)
BackgroundLipoblastoma is a benign tumor of embryonal fat tissue that typically affects children under the age of 3 years. The impact of lipoblastoma on the body largely depends on the tumor’s location and its involvement with adjacent organs. Mediastinal lipoblastoma, a relatively rare form, often presents with dyspnea and difficulty breathing, however, airway involvement has not been previously reported.Case presentationWe describe a 4-month-old female infant diagnosed with lipoblastoma in the mediastinum and endotracheal region, leading to progressive upper airway obstruction and dyspnea. Diagnosis was confirmed through imaging and histopathological analysis. The patient underwent a series of treatments, including bronchoscopic-guided endotracheal intubation with ventilator-assisted ventilation, ECMO-supported mass resection, and airway reconstruction. The patient ultimately achieved complete recovery, with no tumor recurrence observed at a 2-month follow-up.ConclusionMediastinal lipoblastoma can be a significant cause of upper respiratory obstruction and respiratory distress in children. The potential for tracheal infiltration, as seen in this case, has not been previously reported and can pose a life-threatening risk. Recognizing and understanding this rare presentation is essential for timely diagnosis and effective management of this condition.